Pengembangan Aplikasi Nilai Rapor Digital Yayasan Gerai Yatim Dhuafa Berbasis Web Menggunakan Metode Waterfall - Irpan Kusyadi; Endar Nirmala; Mohammad Kevin Putra Adiyaksa; Alexius Grennantoro; Eltyes Michael Efata Zebua; Rivansyah Rivansyah (Teknik Informatika Universitas Pamulang, 2022)
At the Yayasan Gerai Yatim Dhuafa, every semester that has been running, there will be a time when parents and their children receive the results of learning for one semester through the media of report cards. The report card is usually written using a pen/marker filled in by the teaching teacher. When filling out report cards, there are usually some difficulties that occur, such as typos, scribbles, out of markers, and so on. This paper is made to formulate these problems with the aim of making an application that can solve the problems that still occur today. The application that will be made is expected to be able to complete and make it easier for teachers to fill in the values of student learning outcomes.